Metamaterial‐inspired low‐profile high‐gain slot antenna. Issue 9 (8th May 2019) - Pandit, Soumen; Mohan, Akhilesh; Ray, Priyadip
Abstract: This article presents a novel polarization‐independent metamaterial (MTM) which is used for the design of a low‐profile high‐gain magnetic dipole antenna operating at 9.8 GHz. The MTM is alike star‐shape and shows low impedance property around the frequency 9.8 GHz. The reference antenna, which is the SIW‐based slot antenna acts as a magnetic dipole antenna and it has peak gain of 3 dBi. The metamaterial‐inspired slot antenna has low‐profile, that is, 0.133 λ 0 at the frequency 9.8 GHz, and peak gain of 8.24 dBi. At the resonance frequency, more than 5 dB gain improvement is achieved in the proposed design. These results are verified with the fabrication of a prototype antenna and measurements. The cross‐polarized radiation is negligibly altered by this gain enhancement method. The proposed antenna can be used in wireless power transfer and LoS communications.